Global impact of the Antarctic ozone hole - Dynamical dilution with a three-dimensional chemical transport model - Prather, Michael; Rind, David; Garcia, Maria M.; Suozzo, Robert (1990)
The hypothesis that, once the Antarctic ozone hole is photochemically generated in the spring, the ozone deficit remains in the stratosphere throughout the year was investigated using a three-dimensional chemical transport model (CTM) for the stratosphere with linearized ozone chemistry. An Antarctic ozone hole was imposed on the basis of observations, and the dynamical dilution of the ozone-depleted air was followed for the next 12 months. The CTM calculations show that the transport of ozone-poor air from the Antarctic vortex results in measurable decreases to column ozone, extending to 30 deg S during the austral summer. By the end of the year, about 70 percent of the initially prescribed ozone deficit is replenished through stratospheric chemistry.